ACTUAL PROBLEMS OF SMALL AND MEDIUM-SIZED ENTREPRENEURSHIP IN UZBEKISTAN AND WAYS TO SOLVE THEM - Байрамова Ширин Рихсибой кизи (European Science Publishing, 2023)
The state examines the main problems of the development of small and medium-sized businesses in Uzbekistan. Based on the problem of SME development, the main measures are considered, the implementation of which will contribute to the further successful development of small and medium-sized businesses.
Keywords: entrepreneurship, small and medium-sized business, economic barriers, economic situation, government support of entrepreneurship.